Spatial development - Klaus Desmet; Esteban Rossi-Hansberg (Fondazione Eni Enrico Mattei (FEEM), 2010)
We present a theory of spatial development. A continuum of locations in a geographic area choose each period how much to innovate (if at all) in manufacturing and services. Locations can trade subject to transport costs and technology diffuses spatially across locations. The result is an endogenous growth theory that can shed light on the link between the evolution of economic activity over time and space. We apply the model to study the evolution of the U.S. economy in the last few decades and find that the model can generate the reduction in the employment share in manufacturing, the increase in service productivity in the second part of the 1990s, the increase in land rents in the same period, as well as several other spatial and temporal patterns.
Keywords: E32; O11; O18; O33; R12; 330; Dynamic Spatial Models; Growth; Innovation; Land Rent Evolution; Structural Transformation; Technology Diffusion; Trade; Raumwirtschaftstheorie; Regionale Entwicklung; Innovationspolitik; Regionaler Strukturwandel; USA